O idoso em longas-metragens de animação: representações e efeitos de sentido - Galvão, Flávia Motta de Paula (2014)
Based on the theoretical framework of the French Discourse Analysis, more specifically, the studies of Michel Pêcheux (1969; 1975; 1983), we critically analyze and problematize the possibilities of representations of the elderly in two feature films, namely: The Triplets of Belleville (2002) and Up (2008). Discourse Analysis, as a theoretical and methodological field, allows the researcher to build an articulated view of the investigated object and its relationship with socio-cultural, political and economic aspects. In this research, we propose to conduct a discursive analysis enabling to understand and explain the predominant sense relations in the constitution of the representations of elderly in the feature films, which determined, for our work, the production of an analysis about a specific social issue grounded in the study of language. Faced with the ideological, economic, and cultural aspects that are interlaced with the issue of the movies, our goal was to analyze the possible representations of the elderly in both feature films, trying to understand how the representation of elderly is configured in the two movies. In this respect, we seek to analyze how old age is signified in the films and the effects of sense that can circulate socially from it, in the production of reader-effects. Furthermore, during the development of our research, we worked with film analysis, symbolic object that signifies culturally. By working with a foundation of symbolic nature not necessarily verbal, we refer to a significant base, whose component belongs to a certain symbolic system (verbal or nonverbal), which makes sense when it enrolls in the order of history, therefore, a component whose sense cannot be determined a priori. Thus, a particular fact or event can be discursivized in different ways and by different forms of language. In both films, it seems that old age is signified in order to produce a certain movement in representations of elderly, elevating it to the unusual, the comic. This is the aspect that allows the elderly to take the place of main character and hero. This lifting to the comic works because it underlies a stereotype of elderly whose striking aspect is the fragility and weakness of his/her physical capability, which can promote laughter. The elderly is also, in a sense, the index of a critic directed to the value that, apparently, Americans have of old age.